Analisis Kualitas Produk, Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pdam Tirtanadi Cabang Padang Bulan Medan - Nurafrina Siregar; Hasrul Hasibuan; Iqbal Agustia Miransyah (CERED Indonesia Institute, 2021)
This study aims to find out how the influence of product quality (X1), price (X2), and service quality (X3) on customer satisfaction (Y) PDAM Tirtanadi Padang Bulan Medan branch. The population in this study are all customers of PDAM Tirtanadi Padang Bulan Medan branch. The number of samples is 100 respondents. This research was conducted from January 2021 to June 2021. This study used quantitative data that was processed with SPSS version 25.0 with multiple linear regression models. data came from respondents who were collected through questionnaires. The results showed that product quality and price partially had a positive and significant effect on customer satisfaction. Product quality, price and service quality simultaneously have a positive and significant effect. 44.2% of customer satisfaction can be explained and obtained from product quality, price and service quality while the rest by other factors. Customer satisfaction has a very strong relationship to product quality, price and service quality.